Budaya baca siswa SMP di era internet - Nurhadi, Nurhadi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
The Internet is believed to have changed reading habits, as deep reading has shifted due to easy access to online content. This research is intended to explore the reading behavior of junior high school students in the Municipality of Malang. The results indicate that reading is not listed as a favorite pastime, as students spend little time reading. The trend shows that students tend to spend more time accessing the Internet in ways that differ from previous practices. The analysis also reveals a positive correlation between reading habits and Internet-related reading variables.